Evaluating taxpayers’ attitude in the new tax environment - Janiszewska, Magdalena (Postawy podatników w nowym otoczeniu podatkowym, 2019)
One of the taxpayers responses to taxation is tax avoidance. Due to its intensification, Polish legislator has adopted a series of legislative measures to tighten the tax system. The aim of the article is to examine to what extent changes made to the tax law and in the operational framework of tax authorities, geared towards the tightening of the tax regime, impact on the attitude of Polish entrepreneurs operating at international level. For the purpose of the survey a hypothesis was formulated stating that factors such as more stringent regulation, higher risk of being audited, more severe penalties, social approval for tax avoidance and the perceived absence of procedural justice are correlated with the degree of approval for tax avoidance. In order to verify the hypothesis, questionnaire-based studies were carried out and their results were subsequently subjected to statistical analysis. The results of the conducted studies demonstrated that the above mentioned factors do not directly translate into the approach to tax avoidance and that the tax avoidance itself is still not seen as something negative by a large majority of the population
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 19-30